Menuju keluarga mandiri dan sejahtera dengan pemahaman keuangan keluarga berbasis syariah - Pravasanti, Yuwita Ariessa; Pratiwi, Desy Nur; Siarno, Si Islam; Siyamto, Yudi (Nur Science Institute, 2025)
Household financial management remains a significant challenge in achieving family welfare, particularly within rural communities. Limited knowledge and ineffective financial practices often lead to unsustainable spending patterns, a lack of savings, and vulnerability to debt. This community service program was conducted in Makamhaji Village, Kartasura, Sukoharjo, involving 38 participants, to enhance residents' understanding and skills in managing family finances in accordance with Islamic principles. The methods applied included participatory counselling, group discussions, and practical simulations of Islamic household budgeting, supported by a pre-test and post-test design to measure program effectiveness. The results demonstrated a significant overall improvement of 45.2% in participants’ financial literacy, particularly in preparing a Sharia-compliant household budget, understanding the concept of an emergency fund, managing income zakat, and avoiding riba in financial transactions. Participant reflections also indicated that participatory and practical simulation methods were highly effective in enhancing awareness and financial capability grounded in Islamic values.